If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1mx = mx + -1n Reorder the terms: -1mx + 8x = mx + -1n Solving -1mx + 8x = mx + -1n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1mx' to each side of the equation. -1mx + -1mx + 8x = mx + -1mx + -1n Combine like terms: -1mx + -1mx = -2mx -2mx + 8x = mx + -1mx + -1n Combine like terms: mx + -1mx = 0 -2mx + 8x = 0 + -1n -2mx + 8x = -1n Add '-8x' to each side of the equation. -2mx + 8x + -8x = -1n + -8x Combine like terms: 8x + -8x = 0 -2mx + 0 = -1n + -8x -2mx = -1n + -8x Divide each side by '-2x'. m = 0.5nx-1 + 4 Simplifying m = 0.5nx-1 + 4 Reorder the terms: m = 4 + 0.5nx-1
| -2+8=-26 | | M/2-5=5 | | 4x-12+120=180 | | 2x^2-2xy+3y^2=8 | | a+60=6a+20 | | z-16=-9 | | -279=-7(-5b+4)-6 | | U/3,14=70 | | -4(t)=2t-5 | | -(k-1)+2(-2+7k)=8k+8k | | W-4/2/5=9/3/5 | | logx=-4.76 | | z^2+(2+7i)z+(-11+7i)=0 | | 4x+2=2x+x | | 50(60-10)=60 | | 9-3k=5k+1 | | -9x^2-24x+27=0 | | -12=-5x+7x | | 5x-30/24-4x | | (-x^2)-8x+48=0 | | .53333333= | | 8x+29=-21+3xAfspil | | 2x+y=2y+3x-1 | | -5x+2+3x=22 | | -13=v-1 | | 3x+y=2y+3x-1 | | 2n+7-3n+2= | | 10+2x+2x=46 | | 8-4x-4x=-48 | | 2x+y-6=6x+3y-12 | | 2b+8=54 | | 9x-9=6x+18 |